The Belgrade opus of architect Aleksandar Stjepanović: Residential architecture (1961-1992) - Banković Angelina (Nasleđe)
The paper presents the Belgrade realizations of Aleksandar Stjepanović in the field of residential architecture. Although he is among the most prominent creators of the second half of the 20th century, especially in the field of residential architecture, to date no research has been published that presents Stjepanović's complete opus. Therefore, the goal of this work is to identify and briefly present all realized residential buildings on which the architect worked, both independently and as part of a team, in a single place and in accordance with the currently available data. The paper was written based on the results of previous research, technical documentation preserved in protection institutions, archives of city municipalities, and in the documentation of the architect himself, on the basis of conversations with him, as well as field research. A short biography of the architect is given, followed by a summation of the most significant features of residential construction during the time of his activity. Following this, residential buildings that have been realized in Belgrade for which he was engaged in the design process are presented, with a more detailed analysis in relation to both the form and the internal organization of individual housing units also being provided.